G329(P) Causes of mortality in individuals with tuberous sclerosis complex (TSC). (27th April 2016) - Amin, S; Calder, N; Laugharne, M; Osborne, J; O'Callaghan, F
Abstract : Objectives: The causes of death in this group of patients have rarely been studied with the one published account from the Mayo Clinic appearing in 1991. We aimed to investigate mortality in a large clinical cohort of TSC patients to see whether causes of mortality have changed over time. Methods: We have identified 284 TSC patients from our database at the Bath TSC clinic who have attended the clinic from 1981 to the present day. We reviewed the medical notes and if applicable, death certificates and post-mortem reports. Results: 16 died secondary to complications of TSC: eight from TSC kidney complications; four from SUDEP; two from lymphangioleiomyomatosis; one secondary to a SEGA; and one from a pancreatic malignancy. The median age of death was 33 years (IQR 26–46). No one died in the paediatric age range. Mortality was significantly more common in the learning difficulty than the non-learning difficulty patients (9% vs 2%, p = 0.02). Conclusion: Renal disease is a major cause of mortality. Lifelong surveillance of renal lesions and early intervention is warranted. SUDEP is also a significant cause of mortality. LD patients are at significantly greater risk of early mortality and thus implies the need for greater vigilance for TSC related complications in this group. Female patients are vulnerable to pulmonary and renal disease. All post-pubertal female patients should be screened for LAM and treated where appropriate. Pancreatic lesions are also a rare and potentially treatable cause of mortality.